Big Data and Artificial Intelligence in Digital Finance Increasing Personalization and Trust in Digital Finance using Big Data and AI - Soldatos, John.; Kyriazis, Dimosthenis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book presents how cutting-edge digital technologies like Machine Learning, Artificial Intelligence (AI), and Blockchain are set to disrupt the financial sector. The book illustrates how recent advances in these technologies facilitate banks, FinTechs, and financial institutions to collect, process, analyze, and fully leverage the very large amounts of data that are nowadays produced and exchanged in the sector. To this end, the book also introduces some of the most popular Big Data, AI and Blockchain applications in the sector, including novel applications in the areas of Know Your Customer (KYC), Personalized Wealth Management and Asset Management, Portfolio Risk Assessment, as well as variety of novel Usage-based Insurance applications based on Internet-of-Things data. Most of the presented applications have been developed, deployed and validated in real-life digital finance settings in the context of the European Commission funded INFINITECH project, which is a flagship innovation initiative for Big Data and AI in digital finance. This book is ideal for researchers and practitioners in Big Data, AI, banking and digital finance. Introduces the latest advances in Big Data and AI in Digital Finance that enable scalable, effective, and real-time analytics; Explains the merits of Blockchain technology in digital finance, including applications beyond the blockbuster cryptocurrencies; Presents practical applications of cutting edge digital technologies in the digital finance sector; Illustrates the regulatory environment of the financial sector and presents technical solutions that boost compliance to applicable regulations; This book is open access, which means that you have free and unlimited access.
Introduction -- Part I: Novel Big Data and AI Technologies for Digital Finance -- A Reference Architecture for Big Data Systems and AI Applications in the Finance Sector -- Hybrid Transactional and Analytical Processing for Integrated Data Management in Digital Finance and FinTech Applications -- Semantic Interoperability Modelling for Digital Finance Applications -- Semantic Streaming for Digital Finance Applications -- Part II: Blockchain Technologies and Digital Currencies for Digital Finance Applications -- Central Bank Digital Currencies and a Euro for the Future -- Efficient and Accelerated KYC Using Blockchain Technologies -- Part III: Applications of Big Data and AI in Digital Finance -- AI-based platform for Intelligent and Automated Accounting -- Addressing Intra-Day Volatility in Risk Assessments for Forex Trading -- Next-Generation Personalized Investment Recommendations -- Personalized Finance Management for Small Medium Businesses -- AML/CF supervision empowered by AI -- AnalyzingLarge Scale Blockchain Transaction Graphs for Fraudulent Activities -- Cybersecurity and Fraud Detection in Financial Transactions -- Part IV: Applications of Big Data and AI in Insurance -- Risk assessment for personalized health insurance products -- Alternative Data for Personalized Insurance products -- Part V: Technologies for Regulatory Compliance in the Finance Sector -- AI Governance -Trustworthy and Responsible use of AI -- Large Scale Data Anonymization for GDPR Compliance -- Conclusion.
Keywords: Telecommunication; Artificial intelligence; Big data; Business information services; Communications Engineering, Networks; Artificial Intelligence; Big Data; IT in Business